Doxycycline Attenuates Leptospira-Induced IL-1β by Suppressing NLRP3 Inflammasome Priming - Zhang, Wenlong; Xie, Xufeng; Wu, Dianjun; Jin, Xuemin; Liu, Runxia; Hu, Xiaoyu; Fu, Yunhe; Ding, Zhuang; Zhang, Naisheng; Cao, Yongguo (Frontiers in Immunology, 2017)
Doxycycline (Dox), a semisynthetic antibiotic, has been reported to exert multiple immunomodulatory effects. Treatment with doxycycline has a satisfactory curative effect against leptospirosis. In addition to its antibacterial action, we supposed that doxycycline also modulated immune response in controlling leptospira infection. Using J774A.1 mouse macrophages, the effects of doxycycline on protein and mRNA levels of IL-1β and TNF-α were investigated after infection with live or sonicated Leptospira interrogans serovar Lai strain Lai (56601). Specifically, the level of IL-1β but not TNF-α was sharply decreased when treated with doxycycline in leptospira-infected macrophages. Western blot analysis showed that doxycycline suppressed the activation of leptospira-induced MAPK and NF-κB signaling pathways. Using NLRP3-deficient and NLRC4-deficient mice, the data showed that the expression of leptospira-induced IL-1β was mainly dependent on the presence of NLRP3 inflammasome in macrophages. Meanwhile, doxycycline suppressed leptospira-induced NLRP3 inflammasome priming with the up regulation of the Na/K-ATPase Pump β1 subunit. The inhibition effect of doxycycline on IL-1β was also conspicuous in cells with LPS and ATP stimulation. These results were confirmed in vivo, as peritoneal fluids of mice and organs of hamsters expressed less IL-1β after treatment of leptospiral infection with doxycycline. Our results indicated that doxycycline also modulated immune response to attenuate leptospira-induced IL-1β by suppressing p38, JNK, p65 and NLRP3 inflammasome priming.